Study of IRF6 and 8q24 region in non‐syndromic oral clefts in the Brazilian population. (1st February 2016) - de Souza, LT; Kowalski, TW; Ferrari, J; Monlléo, IL; Ribeiro, EM; de Souza, J; Fett‐Conte, AC; de Araujo, TK; Gil‐da‐Silva‐Lopes, VL; Ribeiro‐dos‐Santos, ÂKC; dos Santos, SEB; Félix, TM
Abstract : Objectives: We investigated the association between non‐syndromic oral cleft and variants in IRF6 (rs2235371 and rs642961) and 8q24 region (rs987525) according to the ancestry contribution of the Brazilian population. Subjects and methods: Subjects with oral cleft (CL, CLP, or CP) and their parents were selected from different geographic regions of Brazil. Polymorphisms were genotyped using a TaqMan assay and genomic ancestry was estimated using a panel of 48 INDEL polymorphisms. Results: A total of 259 probands were analyzed. A TDT detected overtransmission of the rs2235371 G allele ( P = 0.0008) in the total sample. A significant association of this allele was also observed in CLP ( P = 0.0343) and CLP + CL ( P = 0.0027). IRF6 haplotype analysis showed that the G/A haplotype increased the risk for cleft in children (single dose: P = 0.0038, double dose: P = 0.0022) and in mothers (single dose: P = 0.0016). The rs987525 (8q24) also exhibited an association between the A allele and the CLP + CL group ( P = 0.0462). These results were confirmed in the probands with European ancestry. Conclusions: The 8q24 region plays a role in CL/P and the IRF6 G/A haplotype (rs2235371/rs642961) increases the risk for oral cleft in the Brazilian population.